Effects of reducing EU agricultural support payments on production and farm income in Finland - Lehtonen, Heikki Sakari; Niemi, Jyrki Sakari (Agricultural and Food Science, 2018)
The budget for the Common Agricultural Policy (CAP) of the EU, and thus EU agricultural support payments, may be reduced from 2021. In this study we analyse the effects this may have in Finland using an economic model of Finnish agriculture accounting for structural changes in the dairy and beef sectors. Reducing the CAP budget by 20% would affect farm incomes by 20–25% in southern Finland while central and northern parts of the country, which are dependent on national payments coupled to dairy and beef production, would be less affected. Our results show that the milk and beef sectors throughout the country are still dependent on support payments coupled to production due to reduced real prices for agricultural products. Current policy schemes for southern Finland include coupled CAP payments but do not allow national payments. Any cuts in the CAP budget have significantly more negative effects in southern Finland compared to other regions.